Bejan’s Constructal Theory of Shape and Structure - Miguel, A, F. (2012)
Introduction; Chapter 1. River Basins: Geomorphology and DynamicsChapter 2. Tree-Shaped Flow Structures for Human-Scale and Small-Scales Applications; Chapter 3. Dendritic Growth: Classical Models and Constructal Analysis; Chapter 4. Thermodynamic Formulation of the Constructal; Chapter 5. Performance Evaluation of Some Passive Augmentation Techniques Using Entropy Generation Minimization Method Law; Chapter 6. Visualization of Two-Dimensional Heat and Mass Transfer using the Heatlines and Masslines; Chapter 7. Constructal View of Global Circulation and Climate; Chapter 8. Entropy Generation for the Next Generation